Dostopnost pravnega varstva pred Državno revizijsko komisijo - Bratina, Tanja (Podjetje in delo, 2016)
The article presents the accessibility of the legal protection/remedies in public procurement procedures, particularly in the light of the mandatory components of the request for audit, the amount of the fees, the limitation of legal protection in relation to certain violations and legal standing. The article presents where the biggest obstacles to "access to justice" can arise, where also the interpretation of the National Review Commission for Reviewing Public Procurement Award Procedures is illustrated relating to specific issues that may have a significant impact on "access to justice".
Keywords: Državna revizijska komisija; odločbe; pravno varstvo; pritožba; revizija